Financial Risk in Off-bottom Oyster Culture along Florida’s West Coast - Russel Dame; Leslie Sturmer; Charles Adams; Richard Weldon; Kelly A. Grogan (EDIS)
This 10-page fact sheet written by Russel Dame, Leslie N. Sturmer, Charles M. Adams, Richard Weldon, and Kelly A. Grogan and published by the UF/IFAS Food and Resource Economics Department explains how to assess the risks involved with off-bottom oyster culture, a method allowing for growing oysters in mesh containers above the sea bottom where they are protected from predation and from becoming buried in sediment. https://edis.ifas.ufl.edu/fe1070